Differences in outcome of patients with syncytial variant Hodgkin lymphoma compared with typical nodular sclerosis Hodgkin lymphoma. (January 2017) - Sethi, Tarsheen; Nguyen, Van; Li, Shaoying; Morgan, David; Greer, John; Reddy, Nishitha
Background: Nodular sclerosis Hodgkin lymphoma (NS-HL) is the most common subtype of HL and usually has a good prognosis. A variant of NS, the syncytial variant (SV) has well-established histopathologic features but little is known about its clinical behavior. Small case series have suggested that SV patients present with advanced disease and have a comparatively aggressive course. The objective of this study was to determine the clinical characteristics and outcome of SV patients Methods: A total of 167 adult patients with NS-HL including 43 patients with SV and 124 patients with typical NS (t-NS) were included in our analysis following institutional review board (IRB) approval. The Kaplan–Meier method was used to calculate the progression-free survival (PFS) and overall survival (OS). Log-rank test was used to determine the differences in survival. Results: Of the 167 patients, 43 were confirmed as SV based on morphology and immunophenotype. Doxorubicin, bleomycin, vinblastine and dacarbazine (ABVD) was the most frequent induction regimen administered in 91% of all patients. The rate of complete response (CR) in the SV group was 74% versus 87% in the t-NS group ( p = 0.05). At 49 months follow up, the PFS was 17 months in the SV group and not reached in the t-NS group [ p < 0.0001; hazard ratio (HR) = 3.695; 95% confidence interval (CI) = 3.0, 11.07]. The median OS was not reached in both groups ( p = 0.32). Conclusions: Our results show that SV histology represents a poor risk group with lower CR rate and shorter PFS and this should be considered in the risk stratification of classical HL patients.